The Island of Cyclopian Saints: Cultural Nationalism and Religion in the “Cyclops” Episode of Joyce’s Ulysses - Gula, Marianna (FOCUS: Papers in English Literary and Cultural Studies, 2024)
“Good puzzle would be cross Dublin without passing a pub,” thinks Leopold Bloom in the early morning of 16 June 1904. It would be an equally good puzzle to work one’s way through the amassed criticism on the “Cyclops” episode ofJoyce’s Ulysses without passing a reference to Irish nationalism. The chapter’s engagement with Irish nationalism, noted by the first commentators, has remained one ofthe crucial issues of critical inquiry up to the present. The nature of this engagement has been continually reassessed, particularly vigorously after the introduction of the concerns and methods of postcolonialism into Joyce criticism in the early 1980s. This process of reappraisal has evinced a clear shift from associating nationalism with the xenophobic citizen’s intolerance and violence against Bloom to problematizing the issue by contextualised readings accommodating the discourses of empire as well as cultural nationalism, and by discussing formal features in terms of engagement with ideological formations, among others those of nationalism.